Biodiesel Production from Cassia tora Seed Oil Through Acid-Base Catalysed Method - Abubakar, Hayatuddeen; Hammari, Abubakar Muhammad; Abubakar, Aisami; Maiwada, Amina (Journal of Biochemistry, Microbiology and Biotechnology, 2021)
Biodiesel produced from different triglyceride sources is an alternative fuel to petro-diesel. An investigation was carried out with Cassia tora seed oil. The oil was esterified to reduce the FFA content in the oil and trans-esterification of the oil was carried out which involves making use of methanol and sodium hydroxide pellets in a base-catalyzed trans-esterification reaction. 187g Cassia tora oil was trans-esterified with 20 g of methanol and 0.7 g of NaOH pellets at 55Â°C operating temperature. The outcome was a percentage conversion of 90.53 per cent for Cassia tora feedstock and a by-product of 15.20 g of glycerol (i.e. soap). The physical features of the oil, such as smell and colour, were retained in the biodiesel produced. The density of biodiesel made from Cassia tora oil was determined to be 848.0 kg/m3. The flashpoint was determined to be 135 oC and the acid value and water content were 0.16 (MgKOH/g) and 0.04 (per cent mass), respectively. The kinematic and dynamic viscosities of the generated biodiesel were 4.2mm2/s and 6.49 x 10-3kgm-1s-1, respectively. The pour point was also discovered to be -6 oC. The biodiesel was evaluated using American testing and material standards (ASTM Values). Based on the comparison of measured characteristics with ASTM values, Cassia tora seed oil could be a promising option for biodiesel production